A rebuttal to Akabayashi and colleagues’ criticisms of the iPSC stock project - Fujita, Misao (Journal of medical ethics, 2019)
In the October edition of the Journal of Medical Ethics, Akabayashi and colleagues state that ’to establish a heterogeneous [induced pluripotent stem cell] iPSC bank covering roughly 80% of Japan’s population…the Japanese government decided to invest JPY110 billion (US$ 1.1 billion) over 10 years in regenerative medicine research; a quarter of this was to be allocated to the iPSC stock project'. While they claim this amount of money to be an unfair distribution of state resources, we believe their assessment is based on a misunderstanding of the facts. Similarly, other criticisms by them are based on mistaken interpretations. This article is a rebuttal to the arguments that form the basis of Akabayashi and colleagues’ five criticisms by explaining their misinterpretations.